Recent Developments in Solar Thermal Desalination Technologies: A Review - Ullah, Ihsan; Rasul, Mohammad G. (Energies (Basel), 2019)
Fresh water resources are depleting rapidly as the water demand around the world continues to increase. Fresh water resources are also not equally distributed geographically worldwide. The best way to tackle this situation is to use solar energy for desalination to not only cater for the water needs of humanity, but also to offset some detrimental environmental effects of desalination. A comprehensive review of the latest literature on various desalination technologies utilizing solar energy is presented here. This paper also highlights the environmental impacts of desalination technologies along with an economic analysis and cost comparison of conventional desalination methods with different solar energy based technologies. This review is part of an investigation into integration of solar thermal desalination into existing grid infrastructure in the Australian context.